The Comparison of the Effect of Risedronate and Strontium Ranelate on Bone Mineral Density in Postmenopausal Women - Figen Yılmaz; Beril Doğu; Hülya Şirzai; Banu Kuran (Galenos Yayinevi, 2012)
Aim: The purpose of our study is to compare the changes in bone mineral density (BMD) in postmenopausal women who had uninterrupted risedronate sodium and strontium ranelate treatment for 3 years. Material and Methods: Eighty-five postmenopausal women with primer osteoporosis who had uninterrupted risedronate sodium (A) (35 mg/week), strontium ranelate (P) (2 g/day) and calcium (1000 mg/day) - vitamin D (880 IU/day) supplementation for 3 years were included in our retrospective study. The demografic data and the yearly BMD measurements (lumbar spine, femur neck and femur total BMD and t scores) were recorded. Results: Group A had 34, and Group P had 51 patients. The mean age of the patients were 62.06±9.16 years and 60.30±7.68 years; and duration of menopause was 16.32±7.81 years and 16.78±8.34 years, respectively. There was statistically no significant difference between the groups regarding age, weight, body mass index, duration of menopause, menarche and menopause age, the lumbar spine, femur neck and total BMD and t scores at the beginning. At the end of uninterrupted 3 years of treatment, statistically significant increase was detected in lumbar spine and femur BMD measurements in Groups A and P (p<0.0001). Statistically significant increase was detected also in lumbar spine t scores in both groups. However, the femur t scores were found not to improve significantly in Group A, while in P, there was significant improvement. When the differences of improvement were compared, there was no difference between Group A and P regarding lumbar spine and femur BMD improvements. Conclusion: There was significant improvement in lumbar spine and femur BMD for Groups A and P at the end of 3 years of treatment for both medical agents, and improvement is similar for both agents. (Turkish Journal of Osteoporosis 2012;18: 58-62)